Transcription Factor-Based Biosensor for Dynamic Control in Yeast for Natural Product Synthesis - Zhang, Yiming; Shi, Shuobo (Frontiers in Bioengineering and Biotechnology, 2021)
The synthesis of natural products in yeast has gained remarkable achievements with intensive metabolic engineering efforts. In particular, transcription factor (TF)-based biosensors for dynamic control of gene circuits could facilitate strain evaluation, high-throughput screening and adaptive laboratory evolution for natural product synthesis. In this review, we summarized recent developments of several TF-based biosensors for core intermediates in natural product synthesis through three important pathways, i.e. fatty acid synthesis pathway, shikimate pathway, and methylerythritol-4-phosphate (MEP)/ mevalonate (MVA) pathway. Moreover, we have shown how these biosensors are implemented in synthetic circuits for dynamic control of natural product synthesis, and also discussed the design/evaluation principles for improved biosensor performance.